Pure de novo partial trisomy 6p in a girl with craniosynostosis1. Issue 2 (10th January 2013) - Varvagiannis, Konstantinos; Stefanidou, Amalia; Gyftodimou, Yolanda; Lord, Helen; Williams, Louise; Sarri, Catherine; Pandelia, Efi; Bazopoulou‐Kyrkanidou, Euterpe; Noakes, Charlotte; Lester, Tracy; Wilkie, Andrew O.M.; Petersen, Michael B.
Abstract Duplications of chromosome 6p are rarely reported. We present the case of a girl with a de novo trisomy 6p12.3–p21.1 who showed clinical features characteristic of this syndrome, notably facial anomalies, psychomotor delay, and recurrent respiratory tract infections. The most striking feature, however, was craniosynostosis, manifested by the premature fusion of the right coronal and sagittal sutures. A review of the literature revealed that the presence of abnormal fontanelles and sutures is relatively common among patients with proximal trisomy 6p. Exclusion of the most frequently occurring craniosynostosis mutations, as well as of further chromosomal anomalies in our case, suggest the presence of a gene regulating suture formation within this region. Based on recent findings, we hypothesize that the runt‐related transcription factor 2 (RUNX2) may be a reasonable candidate gene for craniosynostosis in such patients. © 2013 Wiley Periodicals, Inc.